Pendampingan Penyusunan Jurnal, Buku Besar, Dan Laporan Keuangan Pada Kelompok Tani Pe Belek Selaparang - Abdurrahim; Samsul Hadi (Indonesia, 2024)
The Pe Belek Selaparang Farmer Group in Selaparang District, East Lombok, faces challenges in financial management due to low financial literacy and manual accounting practices. This study aims to provide assistance in the preparation of journals, general ledgers, and financial reports for the farmer group. The method used is a qualitative approach, with interviews, observations, and direct training for 50 group members. The results show that this assistance successfully improved the group’s financial management skills, transparency, and accountability. Additionally, social change emerged with the rise of local leaders who are better prepared to manage finances. In conclusion, the program has successfully enhanced the financial literacy of the farmer group and improved their financial management.